2022
DOI: 10.1039/d1tc06005h
|View full text |Cite
|
Sign up to set email alerts
|

Multi-factor-controlled ReRAM devices and their applications

Abstract: Resistive random access memory (ReRAM) based on resistive switching (RS) effect is a new type of non-volatile memory device that stores information based on the reversible conversion of resistance states...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 209 publications
0
16
0
Order By: Relevance
“…In Figure 7 c, the released oxygen ions were driven by the electric field to the conductive metallic filament, leading to the rupture of the filament due to an oxidation reaction. Finally, the resistance state of the thin film from RRAM devices switched from LRS to HRS to complete the reset process [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 7 c, the released oxygen ions were driven by the electric field to the conductive metallic filament, leading to the rupture of the filament due to an oxidation reaction. Finally, the resistance state of the thin film from RRAM devices switched from LRS to HRS to complete the reset process [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering the above issues, the existing limitations of photoelectric memristors are analyzed, and the key to the development of these technologies lies in the selection of materials and the design of device structures. , At the material level, it can be seen that two-dimensional (2D) materials, perovskite materials, inorganic materials, organic materials, biomaterials, etc. can be used to prepare high-performance memristors. − However, some technical problems and inherent defects of the materials still affect the further development of photoelectric memristors to some extent. For example, for 2D materials, although it has been reported that 2D materials can be grown at the wafer scale, the problem of large-scale and high-quality growth of 2D materials is still a problem to be solved due to the immaturity of growth technology and the low material transfer efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, a memristor is a two-terminal electrical device that is expected to dynamically change its internal resistance state (from high- (HRS) to low-resistance states (LRS) and vice versa) depending on the history of applied electrical stimuli (voltage and/or current). Interestingly, when the optical stimulus is introduced as an additional external stimulation to regulate the growth and dissolution of the conductive filaments in the active layer, the local conductivity can be modified by the synergistic interplay between the electrical and optical means. , Such a functional integration of an optical sensor and a resistive memory provides a new platform to integrate different nanosensors with in-built memory in a single device. These systems are well-known as optoelectronic or photonic memristors which offer several advantages over conventional resistive switching devices .…”
Section: Introductionmentioning
confidence: 99%